Factor structure of the patient health questionnaire-4 in adults with attention-deficit/hyperactivity disorder - Havnen, Audun; Lydersen, Stian; Mandahl, Arthur; Lara-Cabrera, Mariela Loreto (Frontiers in Psychiatry, 2023)
Background: Persons with attention-deficit/hyperactivity disorder (ADHD) frequently experience symptoms of anxiety and depression. In this population, there is a need for validated brief self-report screening questionnaires to assess the severity of comorbid mental health problems. The Patient Health Questionnaire 4 (PHQ-4) is a self-report questionnaire that may contribute to this purpose as it can screen for both disorders efficiently. However, this will be the first study examining the factor structure of the PHQ-4 in samples of adults with ADHD, and also evaluating the validity of the Norwegian version of the PHQ-4.The aim of the current cross-sectional study was to examine the factor structure and validity of the Norwegian version of the PHQ-4 in a sample of adults who reported having been diagnosed with ADHD.Methods: Of 496 invited, a total of 326 participants (66 %) completed the PHQ-4, The World Health Organization Five Well-Being Index, the Oslo Social Support Scale and the 4-item Perceived Stress Scale electronically in a web-portal between the 9 th and 30 th of June 2020.Results: Confirmatory factor analysis of the PHQ-4 supported a two-factor structure (RMSEA = 0.038 [90% CI 0.000-0.159], CFI = 1.00, TLI = 0.999, SRMR = 0.004), consisting of a depression factor and an anxiety factor. Standardized factor loadings were 0.79 to 0.97. The PHQ-4 was negatively correlated with well-being and social support and positively correlated with perceived level of stress.This study indicates promising psychometric properties of the PHQ-4 as a measure of anxiety and depressive symptoms in adults with self-reported ADHD who are fluent in Norwegian. The questionnaire's brevity makes it a valuable resource in research and clinical settings. However, more studies are needed to test the instrument in a clinical sample.